2019
DOI: 10.3390/cosmetics7010002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Sensory Interpretation of Rheological Parameters of a Cream Formulation

Abstract: As the popularity of a cosmetic product on the market extensively depends on consumers’ perception, it is important for the sensory evaluation to be accurate during the product developmental stage. The focus of this study was to develop a generic method for the quantitative assessment of the sensory attributes of cosmetic creams. Four 100 g oil-in-water (O/W) model creams, containing loaded niosomes and their baselines (without niosomes), were formulated. Quantitative sensory evaluation of the formulated oil-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The texture and sensory performance of a personal care product depend in part on the interplay of G ′ and G ″ frequency response. By measuring the two moduli, they can give insight on the sensorial characteristics of a product [27]. The higher the elastic modulus, the more stiffer and elastic the perception of the product usually is.…”
Section: Resultsmentioning
confidence: 99%
“…The texture and sensory performance of a personal care product depend in part on the interplay of G ′ and G ″ frequency response. By measuring the two moduli, they can give insight on the sensorial characteristics of a product [27]. The higher the elastic modulus, the more stiffer and elastic the perception of the product usually is.…”
Section: Resultsmentioning
confidence: 99%
“…In the flow loop experiments, 60s' intervals were applied between each curve, being this an insufficient time to check the fully recovery of samples. However, the results of time‐dependent behavior of the samples are good indication of spreadability, since cosmetic products are rapidly absorbed when applied to skin (Adejokun and Dodou, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we demonstrated how sensory attributes of semisolids, such as pourability, firmness, elasticity, spreadability and stickiness, can be accurately correlated to the rheological measurements of the formulation [7]. In this study, we aimed to develop further such correlations.…”
Section: Introductionmentioning
confidence: 93%
“…However, user trials involving scoring scales can be biased due to the subjective nature of the collected data [5,6]. Therefore, there is a need for the development of instrumental techniques that can reliably correlate to and predict sensory properties [7].…”
Section: Introductionmentioning
confidence: 99%